Redefining the greenness of quantitative analytical methods for drugs: A case study of a multipurpose novel janus kinase inhibitor - Sagar Suman Panda (Green Analytical Chemistry)
Greenness has become a popular term in the field of analytical chemistry, with significant advancements in measuring the greenness of methods. Several newer approaches are exploring the different practical aspects of measuring the greenness of newly developed analytical procedures. However, conducting a retrospective greenness assessment of older methods can be beneficial and cost-effective in achieving sustainable method performance within the regulatory framework. The current study highlights the significance of evaluating greenness using various existing greenness metrics. Furthermore, it presents a case study that assesses the greenness of various reported methods and a newly developed systematic infrared spectroscopic method for a novel drug, baricitinib. The designed experiments-oriented infrared method development offered a robust framework for optimizing and validating the method, assuring robustness and reliability of results while minimizing resource demand, overall developmental time, and method failure. The recent method's linearity, accuracy, and precision were acceptable, and sophisticated sample preparation was not required. Finally, it addresses several practical challenges and gaps that can be overcome by some of the necessary revisions in the existing procedures. In summary, this study raises awareness among the analyst community about the importance of adopting the greenness metrics approach, for newly developed methods and existing methods, in order to achieve predefined method performance throughout the method lifecycle and support green initiatives.